Thoracoscopic excision of asymptomatic antenatally diagnosed mediastinal bronchogenic cysts: A case report - Elisa Cerchia; Carmine Noviello; Giovanni Torino; Edoardo Bindi; Francesca Mariscoli; Giovanni Cobellis (PAGEPress Publications, 2021)
Bronchogenic Cysts (BCs) are benign congenital malformations commonly located in the mediastinum. In recent years the development of antenatal diagnosis has changed the BCs management allowing an earlier minimally invasive approach. We report a case of an asymptomatic 8-months-old girl with antenatal diagnosis of subcarinal posterior mediastinal BC. Thoracoscopic excision of the cyst was successfully performed. The management of antenatally diagnosed BCs is discussed. Thoracoscopic treatment of BCs is safe and effective with the advantage of a reduced morbidity compared to thoracotomy.